Promoting Exclusive Breastfeeding in Sokoto: The Role of Counseling, Parental Support, and Health Education - Musa, Shamsuddin; Sarkingobir, Yusuf; AI, Umar; Abubakar Abdullahi, Mukhtar (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study aims to investigate exclusive breastfeeding (EBF) in Sokoto. Design/methods/approach – A survey type of 300 respondents was used; data were analyzed with frequency counts/percentages and an X2 test. Findings – All respondents were female (100.0%), aged 26-35 (100.0%). The majority of the participants were single (66.7%) and unemployed (66.7%), with a secondary school education (66.7%). However, 33.3% of the participants were married, were civil servants, and had tertiary education. The study revealed that the majority (66.7%) had received breastfeeding counseling during antenatal care. All respondents (100.0%) received proper guidance/counseling at home on exclusive breastfeeding. Fathers (66.7%) and mothers (33.3%) supported exclusive breastfeeding. The respondents reported exclusively breastfeeding their child for the first six months after delivery (100.0%), and weaning occurred between 19-24 months. The reasons for avoiding exclusive breastfeeding were the sickness of the mother (66.7%) and insufficient milk (33.3%). All respondents (100.0%) agreed that exclusive breastfeeding improved the baby’s health, and health awareness encourages breastfeeding (100.0%). Research implications/limitations – This study provides a limit in the form of maximum exclusive breastfeeding for children aged 24 months. Practical implications – The study suggests that counseling, support from parents, and health awareness can improve exclusive breastfeeding, and healthcare providers should provide such services during antenatal care while promoting the practice through health education campaigns. Originality/value – This study highlights the importance of counseling, parental support, and health education in promoting exclusive breastfeeding and improving the health of infants in Sokoto. Paper type Research paper